LEGAL PROTECTION FOR CONSUMERS AGAINST COUNTERFEIT DISCOUNTS PROVIDED ON TWIN DATES BY E-COMMERCE BUSINESS OPERATORS IN INDONESIA - Pranata Bahri, Farizal (Yayasan Meira Visi Persada, 2024)
This research aims to analyze the legal protection for consumers who experience fake discounts during the twin date event in e-commerce. By using a normative juridical research method, conducting a study of legal articles, the KBBI (Great Dictionary of the Indonesian Language), and legal dictionaries, this research concludes that there are several ways to implement consumer protection for those who experience fake discounts during the twin date event in e-commerce. These include the enactment of rolling regulations in Indonesia and the establishment of institutions specifically used to protect consumers. The government has also provided opportunities for consumers who feel aggrieved to settle disputes through criminal or civil courts, as well as through consumer dispute resolution bodies with three settlement options: conciliation, mediation, and arbitration without going through the courts.